Review Inchemical Structures of Drugs - Mahmood Aljamali, Nagham; ., . (International Journal of Engineering and Technology, 2018)
Our reviewÂ concernedÂ withÂ chemicalÂ structuresÂ ofÂ someÂ drugsÂ inÂ Â Â pharmaceuticalÂ fieldsÂ ,someÂ of themÂ usedÂ inÂ syntheticÂ fieldÂ andÂ inÂ synthesisÂ ofÂ manyÂ drugsÂ andÂ Â antibiotics.Â